2021
DOI: 10.35912/ahrmr.v1i2.503
|View full text |Cite
|
Sign up to set email alerts
|

Examining the quality of work life: empirical testing indicators in the public organisation

Abstract: Purpose: The present study aimed to identify employees’ quality of work life indicators in public organisations and provide necessary context to improve system accountability and employees’ needs in organisations. Research methodology: To identify quality of work life indicators, authors studied theoretical research basics entirely and by considering elites’ ideas, identified main indicators by a descriptive – survey technique. Result: Based on research findings, 15 constituents were identified as work lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Bank management should be aware of employee turnover as it has a direct impact on bank customer service and overall profitability. A study conducted by Zahedy, Jafari, and Ramezan (2021) found that safe and healthy working conditions and organizational conflict are the most significant elements, whereas job satisfaction and pay/benefits are the least significant factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bank management should be aware of employee turnover as it has a direct impact on bank customer service and overall profitability. A study conducted by Zahedy, Jafari, and Ramezan (2021) found that safe and healthy working conditions and organizational conflict are the most significant elements, whereas job satisfaction and pay/benefits are the least significant factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, we first analyzed the physical fitness assessment systems of children and adolescents in foreign countries in the past 20 years [6][7][8] to provide theoretical support for the screening of the testing index system. Secondly, after initially determining the testing indexes [9][10][11] and proving their validity through prediction tests, the study seeks the opinions of domestic and foreign experts related to physical fitness and health research as well as relevant practitioners who have been engaged in students' physical fitness and health testing for a long period of time. Finally, we designed and completed the "Screening Questionnaire on Physical Fitness Evaluation Indicator System for Children and Youth" [12][13][14] , which adopts Satty's 9-level scale method to categorize the survey contents into 5 levels, namely, absolutely important, very important, relatively important, a little important, and equally important, corresponding to the scores of 9, 7, 5, 3, and 1, respectively.…”
Section: Screening Of Test Indicatorsmentioning
confidence: 99%
“…Dimensions or indicators of Quality of Work Life are communication, problem solving, career development, employee involvement, a sense of pride in the institution, balanced compensation, safety of the work environment, a sense of job security, facilities obtained (Cascio, 2012). The quality of work life has been studied by many previous researchers including (Al Dalayeen, 2017), (Allam, 2019), (Suwandia & Tentama, 2020), (Agus, 2020), (Zahedi, Jafari, & Ramezan, 2021), and (Srivastava & Kanpur, 2014).…”
Section: Quality Of Work Lifementioning
confidence: 99%